Barriers to Uptake of Insulin Technologies and Novel Solutions - Pauley ME (Dove Medical Press, 2021)
Meghan E Pauley, Cari Berget, Laurel H Messer, Gregory P Forlenza Barbara Davis Center for Childhood Diabetes, University of Colorado Anschutz Medical Campus, Aurora, CO, USACorrespondence: Gregory P ForlenzaBarbara Davis Center for Childhood Diabetes, University of Colorado Anschutz Medical Campus, 1775 Aurora CT, MS A140, Aurora, CO, 80045, USATel +1 303-724-2323Fax +1 303-724-6779Email gregory.forlenza@cuanschutz.eduAbstract: Diabetes-related technology has undergone great advancement in recent years. These technological devices are more commonly utilized in the type 1 diabetes population, which requires insulin as the primary treatment modality. Available devices include insulin pumps, continuous glucose monitors, and hybrid systems referred to as automated insulin delivery systems or hybrid closed-loop systems, which combine those two devices along with software algorithms to achieve advanced therapeutic capabilities, including automatic modulation of insulin delivery based on sensor-derived glucose levels to minimize abnormal glucose trends. Use of diabetes technology is associated with significant positive health and psychosocial outcomes, yet utilization rates are generally lacking across both adult and pediatric type 1 diabetes populations in the United States and other countries. There are consistent themes in existing barriers to technology uptake reported by individuals with type 1 diabetes or parents of children with type 1 diabetes, including physical burdens associated with wearing the devices, concerns in navigating the technology and the devices’ abilities to meet user expectations, high cost, inadequate resources within the healthcare team to support device use, disparities in technology access, and psychosocial barriers. It is important to understand the common barriers to uptake of not only the automated insulin delivery systems but also their component devices (insulin pumps and continuous glucose monitors) to fully support individuals in utilizing these devices and optimizing health benefits. The purpose of this article is to summarize the current automated insulin delivery devices that are available for use in management of type 1 diabetes, review common barriers to uptake of those systems and their component devices, and provide expert opinion on existing and future solutions to identified barriers.Keywords: type 1 diabetes, artificial pancreas, insulin pump, continuous glucose monitor, hybrid closed loop